STUDENT CHARACTER EDUCATION THROUGH THE IMPLEMENTATION OF RELIGIOUS MODERATION IN MADRASAH TSANAWIYAH - Ahmad Rifqi Azmi (STAI Al-Hidayat Lasem, 2025)
The Qur'an is also believed to include this word as al-Salam (a term for Allah the Most Calm), muslim (a person who seeks a peaceful life), silm (harmony itself), Islam (a term for the religion sent by the Prophets). off lifting Allah's expression), so that humans live in harmony with themselves, their families, social networks, the grave, until they enter heaven